2013
DOI: 10.1089/acm.2012.0586
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination in Health Care and CAM Use in a Representative Sample of U.S. Adults

Abstract: Objectives: Discrimination in medical settings may influence patient attitudes about health care and healthseeking behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…The reasons for these behaviours are unclear, however it may be that those who are combining herbal medicines with pharmaceuticals are concerned about disclosing this to their health care providers for fear of discrimination. Discrimination in health care was found to be related to self-prescribed herbal medicine use in a representative sample of US adults [ 28 ]. In addition, being dissatisfied with the medical encounter has been found to predict CAM use in both cancer [ 29 , 30 ] and general population samples [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for these behaviours are unclear, however it may be that those who are combining herbal medicines with pharmaceuticals are concerned about disclosing this to their health care providers for fear of discrimination. Discrimination in health care was found to be related to self-prescribed herbal medicine use in a representative sample of US adults [ 28 ]. In addition, being dissatisfied with the medical encounter has been found to predict CAM use in both cancer [ 29 , 30 ] and general population samples [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 Data from the 2001 Health Care Quality Survey suggested that individuals who experienced unmet medical needs and discrimination based on ability to pay, ability to speak English, racial or ethnic background, and sex were statistically significantly more likely than other individuals to use CAM (P<.01). 9 Health care workers were more likely than the general population to use all forms of CAM (P<.01). 10 Despite the use of CAM by health care workers, nearly two-thirds of the users have reported not discussing their use of CAM with their physicians.…”
Section: Background and Significance Of Cammentioning
confidence: 96%
“…In addition, researchers found that non-Hispanic black women marginally use chiropractic services more often than men, which is in congruence with existing CAM research overall. 3 Studies have demonstrated that blacks trust the medical system less than whites 42,43 and that health 48,49 This is believed to result in them suffering from higher morbidity and mortality. 49 For example, Schwamm et al 48 performed a study where they found that blacks had lower odds compared to white patients of receiving intravenous thrombolysis, deep vein These were the exact questions asked.…”
Section: Discussionmentioning
confidence: 99%